2021
DOI: 10.1371/journal.pone.0245618
|View full text |Cite
|
Sign up to set email alerts
|

Myogenin is required for assembly of the transcription machinery on muscle genes during skeletal muscle differentiation

Abstract: Skeletal muscle gene expression is governed by the myogenic regulatory family (MRF) which includes MyoD (MYOD1) and myogenin (MYOG). MYOD1 and MYOG are known to regulate an overlapping set of muscle genes, but MYOD1 cannot compensate for the absence of MYOG in vivo. In vitro, late muscle genes have been shown to be bound by both factors, but require MYOG for activation. The molecular basis for this requirement was unclear. We show here that MYOG is required for the recruitment of TBP and RNAPII to muscle gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…These results indicate that the cooperative binding of KLF5 increases H3K27ac levels at the binding sites of these three myogenic factors. Previous research revealed that MYOD, MYOG, and MEF2D sequentially play a role in myogenesis [ 38 , 49 , 50 , 51 ]. We tried to simulate the assembly process of the enhancer transcription machinery during myogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the cooperative binding of KLF5 increases H3K27ac levels at the binding sites of these three myogenic factors. Previous research revealed that MYOD, MYOG, and MEF2D sequentially play a role in myogenesis [ 38 , 49 , 50 , 51 ]. We tried to simulate the assembly process of the enhancer transcription machinery during myogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, their functions are distinct. MYOD first induces chromatin modification, and then MYOG binds to activate gene expression [ 50 , 51 ]. MEF2D lacks independent myogenic activity and requires cooperation with MRF family members to activate the myogenic differentiation program [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than MyoD, late maturation depends mainly on myogenin, and MyoD cannot compensate for the loss of myogenin in vivo. 53 In addition to controlling the maturation of skeletal muscle, myogenin also affected the location and distribution of resident satellite cells, which demonstrated a multilevel contribution of myogenin to muscle homeostasis throughout life. 54 Therefore, the poly(A) polymerase Tent5a might play an important role in maintaining the mRNA stability of myogenin.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that knockout of myomaker and myomixer suppressed the formation of MyHC-positive multinucleated myotubes, which is consistent with our results [ 34 ]. The gene expression of proteins involved in membrane fusion, including myomaker and myomixer, is regulated by myogenin, which is known to bind to the promoter region of these genes and enhance gene expression [ 1 , 11 , 19 ]. In addition, myogenin is a muscle-specific transcription factor regulated by N-cadherin-mediated intracellular signaling, and N-cadherin inhibitors have been found to decrease myogenin protein expression in C2C12 cells [ 6 ].…”
Section: Discussionmentioning
confidence: 99%